2019
DOI: 10.1039/c8sc03390k
|View full text |Cite
|
Sign up to set email alerts
|

The anti-apoptotic proteins NAF-1 and iASPP interact to drive apoptosis in cancer cells

Abstract: We reveal a novel interaction between the two anti-apoptotic proteins iASPP and NAF-1, which are overexpressed in many types of cancer cells, and propose that this interaction is required for apoptosis activation in cancer cells. A peptide derived from the interaction interface inhibits apoptosis in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Investigations are underway to identify those residues in the secondary coordination sphere that might be involved in the stabilization of the CISD2 cluster in the presence of oxygen and its low pH dependency. Interestingly, induction of apoptosis in breast cancer cells leads to CISD2 interaction with the inhibitor of apoptosis-stimulating protein of p53 (iASPP) and a structural model of holo-CISD2 in interaction with iASPP has been proposed [ 31 ]. Prohibition of this interaction by a iASPP-derived peptide also inhibits apoptosis in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations are underway to identify those residues in the secondary coordination sphere that might be involved in the stabilization of the CISD2 cluster in the presence of oxygen and its low pH dependency. Interestingly, induction of apoptosis in breast cancer cells leads to CISD2 interaction with the inhibitor of apoptosis-stimulating protein of p53 (iASPP) and a structural model of holo-CISD2 in interaction with iASPP has been proposed [ 31 ]. Prohibition of this interaction by a iASPP-derived peptide also inhibits apoptosis in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Iosub-Amir and colleagues reported that the NAF1 protein regulates apoptosis through the interaction with the iASPP peptide. It is possible that the increase of the NAF1 gene expression induces the apoptosis that in turn could favor the elimination of defective spermatozoa [ 57 ]. In our study, we observed that the A allele of rs7675998 is associated with an increased percentage of normal sperm suggesting that activation of the apoptotic process could increase the percentage of normal spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Because iASPP is the only interacting partner of the p53 linker domain, using the p53 Linker‐derived peptides can specifically target iASPP and no other proteins in the apoptotic cascade. The RT loop of iASPP plays a major role in the iASPP auto‐activation mechanism, and was found to be an interaction site between iASPP and NAF‐1 in promoting apoptosis in cancer cells . The iASPP RT is thus a “hot spot” on iASPP that can be targeted in order to inhibit iASPP activity in cancer cells.…”
Section: Discussionmentioning
confidence: 99%